Processing of concentrated aqueous zirconia-bioglass slips by slip casting - León, Beltina (2017)
3 mol% yttria-partially stabilized zirconia (Y-TZP) powder and a sol-gel derived CaO–P2O5–SiO2 (64S) bioglass, were used to produce Y-TZP- bioglass slip cast compacts. The rheological properties of concentrated aqueous Y-TZP-64S suspensions prepared with two different glass contents: 10.5 vol% and 19.9 vol%, and ammonium polyacrylate (NH4PA) as dispersant, were investigated and compared with those of Y-TZP. The density of green cast samples was related to the degree of slip dispersion. The substitution of Y-TZP by 64S glass in the mixtures resulted in greater adsorption of NH4PA; however, the viscosity and yield stress values of Y-TZP-64S slips were higher than those of Y-TZP ones for the solid loadings studied. The increase in the glass content from 10.5 to 19.9 vol% increased the viscosity and yield stress values. The presence of 64S glass in the mixtures resulted in a less dense packing of cast samples.